PENERAPAN HISTORY GUIDE PROJECT BERBANTUAN MEDIA SERI PETUALANGAN JANUS UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Eko Prasetyo Utomo (LPMP Provinsi DKI Jakarta, 2023)
This study aims to determine 1) the implementation of the History Guide Project assisted by the Janus Adventure Series media; 2) improving learning outcomes; and 3) increasing student activity. This study followed the procedure of classroom action research. This research was conducted in two cycles. Data collection techniques used in this study include observation sheets and tests. The results showed that there was an increase in the quality of learning by the teacher in the class, namely the first cycle from 87.63% in the very good category to 94.28% in the second cycle in the very good category. Students' cognitive learning outcomes also increased, namely the first cycle with an average value of 80.96 to 85.48 in the second cycle. Student activity also increased, namely the first cycle of 80.83% in the very good category, increasing in the second cycle with a score of 90.83% in the very good category. Based on these results indicate that the combination of models and appropriate learning media can improve the quality of learning in the classroom.